The tobacco GNTI stem region harbors a strong motif for homomeric protein complex formation - Schoberer, Jennifer; Izadi, Shiva; Kierein, Carolina; Vavra, Ulrike; König-Beihammer, Julia; Ruocco, Valentina; Grünwald-Gruber, Clemens; Castilho, Alexandra; Strasser, Richard (Frontiers in Plant Science, 2023)
The Golgi apparatus of plants is the central cellular organelle for glycan processing and polysaccharide biosynthesis. These essential processes are catalyzed by a large number of Golgi resident glycosyltransferases and glycosidases whose organization within the Golgi is still poorly understood.Methods: Here, we examined the role of the stem region from the cis/medial-Golgi enzyme Nacetylglucosaminyltransferase (GNTI) in homomeric complex formation in the Golgi of Nicotiana benthamiana using biochemical approaches and confocal microscopy.Results: Transient expression of the N-terminal cytoplasmic, transmembrane and stem (CTS) region of GNTI leads to a block in N-glycan processing on a co-expressed recombinant glycoprotein. Overexpression of the CTS-region from Golgi α-mannosidase I, which can form in planta complexes with GNTI, results in a similar block in N-glycan processing, while GNTI with altered subcellular localization or N-glycan processing enzymes located further downstream in the Golgi did not affect complex N-glycan processing. The GNTI-CTS dependent alteration in N-glycan processing is caused by a specific nine amino acid long sequence motif in the stem which is required for efficient GNTI-GNTI interaction.Discussion: Taken together, we have identified a conserved motif in the stem region of the key Nglycan processing enzyme GNTI. We propose that the identified sequence motif in the GNTI stem region acts as a dominant negative motif which can be used in transient glycoengineering approaches to produce recombinant glycoproteins with predominately mannosidic N-glycans.